The Influence of Implementing Information Technology on Knowledge Management Toward Performance Evaluation Using Balanced Scorecard - Sarjito Surya (International Conference on Engineering and Technology Development (ICETD), 2014)
Performance Evaluation using Balanced Scorecard already establish in early 1990 introduced by Robert S. Kaplan and David P. Norton. They measured performance evaluation using customer's perspective, internal business perspective, innovation and learning perspective and financial perspective. Balanced scored card give new perspective line beside only financial perspective. Knowledge management efforts typically focus on organizational objectives such as improved performance, competitive advantage, innovation, the sharing of lessons learned, integration and continuous improvement of the organization. Implementing of Information Technology on Knowledge Management can be used to automate and control the process. Learning process as we know is one of three factor for increasing performance. The aim for this research is knowing how far Implementing of Information Technology on Knowledge Management influencing organizational performance.